Density Dynamics and Plankton Diversity in Pond with Different Bases at Faculty of Fisheries and Marine Education Pond - Sukrismiati Sukrismiati; Endang Dewi Masithah; Sudarno Sudarno (Journal of Marine and Coastal Science, 2020)
The availability of plankton in the waters is influenced by nutrient content, and the waters physics-chemical conditions. The higher the nutrient content in a waters, the higher phytoplankton abundance in the waters will be.This research is conducted at faculty of fisheries and marine education pond Airlangga University. It is aimed to density dynamics and plankton diversity in pond with different bases. This research method uses survey method.The reseach results shows that the highest density in tarpaulin pond is located at point four on the first day that reaches 1,822,000 ind/l, The highest total density on the ground pools is got on first day on the first point of 245,000 ind/l.